2020
DOI: 10.1186/s12871-020-00977-0
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction and myocardial injury after major emergency abdominal surgery: a prospective cohort study

Abstract: Background: Preoperative endothelial dysfunction is a predictor of myocardial injury and major adverse cardiac events. Non-cardiac surgery is known to induce acute endothelial changes. The aim of this explorative cohort study was to assess the extent of systemic endothelial dysfunction after major emergency abdominal surgery and the potential association with postoperative myocardial injury.Methods: Patients undergoing major emergency abdominal surgery were included in this prospective cohort study. The primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 29 publications
2
14
1
Order By: Relevance
“…This study reports a secondary outcome from a prospective protocol (ClinicalTrials no. NCT03010969), and the primary outcome has earlier been reported 18,19 . Data were collected from the Department of Surgery at Zealand University Hospital, Denmark.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study reports a secondary outcome from a prospective protocol (ClinicalTrials no. NCT03010969), and the primary outcome has earlier been reported 18,19 . Data were collected from the Department of Surgery at Zealand University Hospital, Denmark.…”
Section: Methodsmentioning
confidence: 99%
“…NCT03010969), and the primary outcome has earlier been reported. 18,19 Data were collected from the Department of Surgery at Zealand University Hospital, Denmark. The protocol was approved by the Danish Local Ethics Committee (no.…”
Section: Population and Study Designmentioning
confidence: 99%
“…We have previously shown that RHI and data variation depend on the type of surgery and population. 3,5,11 The pilot endothelial assessments were performed within the structure of the larger PIXIE trial in order to guide sample size calculations for a future trial with endothelial function as a main outcome. For this pilot sub-study, 20 patients were included in each group.…”
Section: Sample Size and Statisticsmentioning
confidence: 99%
“…While pre‐operative endothelial dysfunction has been associated with the risk of developing perioperative major adverse cardiovascular events 8‐10 the clinical consequences of endothelial dysfunction in the perioperative period remain to be established. Endothelial dysfunction early after surgery may play a role in the pathophysiology of myocardial injury 11 …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation